In the name of the urban poor access to basic amenities - Kundu, Amitabh 1948- (Sage, 1993)
This book analyses the access of the urban poor to five basic amenities - housing, water supply sanitation, health care and the public distribution system. Professor Kundu provides an overview of the existing organisational structure responsible for the provision of these amenities and examines its sensitivity to the needs and affordability of the poor. He concludes that the system has not been designed to meet the minimum needs of the poor and is vulnerable to manipulation by vested interests. Examining in detail the specific programmes and schemes launched by the government, Professor Kundu notes that the stipulations built into them to enable access by the poor are inadequate and superficial. Using published data from the population censuses and the national sample survey, unpublished data from various government departments, the primary data from field surveys, this book also analyses spatial variations in the level of these amenities and their accessibility to the poor in relation to the level of economic development of the states. The author concludes that the poor have been able to get only a small share of these amenities, the non-poor getting the larger share in per capita terms. Further, the poor have access to only the lower order amenities, while the better quality and higher order services are cornered by those in the middle and upper cosumption brackets. Essential reading for those involved in town planning, housing and urban development, urban economics and development in general.
Keywords: Armen (personen); Basisbehoeften; Steden; Stadt; Basic needs -- India; Urban poor -- India; Armut; Grundbedürfnis; Indien